Determination of tamoxifen and its metabolites using micelle to solvent stacking in nonaqueous capillary electrophoresis. Issue 9 (15th March 2016) - Thang, Lee Yien; See, Hong Heng; Quirino, Joselito P.
Abstract : Micelle to solvent stacking was implemented for the recently established NACE‐C 4 D method to determine tamoxifen and its metabolites in standard samples and human plasma of breast cancer patients. For stacking, the standard samples and extract after liquid–liquid extraction (LLE) were prepared in methanol and the resulting sample solution was pressure injected after a micellar plug of SDS. Factors that affected the stacking such as SDS concentration, micelle, and sample plug length were examined. The sensitivity enhancement factor (peak height from stacking/peak height from typical injection of sample in BGE) was 15–22. The method detection limits with LLE were in the range of 5–10 ng/mL, which was lower than the established method (where the LLE extract was also prepared in methanol) with reported method detection limits of 25–40 ng/mL. The intraday and interday repeatability were in the range of 1.0–3.4% and 3.8–6.5%, respectively.